Table 1_From theory to practice: examining the influence of physically active learning on curriculum design and pedagogical planning in initial teacher education.docx - Natalie Lander (7834793) (2025)
Introduction Teacher effectiveness is a critical factor influencing student outcomes, with physically active learning (PAL) emerging as an evidence-based approach that enhances academic achievement and health. Embedding PAL within Initial Teacher Education (ITE) may support pre-service teachers to develop pedagogical competence and confidence. TransformUs Higher Ed is a research-informed intervention designed to integrate PAL within ITE, aligned with the Australian Professional Standards for Teachers—Graduate Level. While prior research shows improvements in pre-service teacher confidence and willingness to use PAL, limited evidence exists on how these strategies are embedded in pre-service teachers' lesson planning. This study explored how components, philosophies, and strategies from TransformUs Higher Ed were incorporated into the lesson planning of first-year Bachelor of Education pre-service teachers at an Australian university. Methods A mixed-methods study was conducted with first-year Bachelor of Education pre-service teachers (N = 141). Participants received the TransformUs Higher Ed program as part of a core Curriculum and Pedagogy unit. Quantitative data were extracted from lesson sequence assessments, capturing inclusion, frequency, type, and purpose of PAL strategies and their alignment with professional standards. Descriptive statistics were generated using Stata SE 18. Qualitative data were drawn from students' video reflections and analysed inductively in NVivo 14. Results Of the 141 participants, 89% incorporated at least one PAL strategy into lesson planning, yielding 447 active strategies (M = 3.17 per student). Active breaks, particularly transition- and structure-based breaks, were more common than active lessons, with experiential learning the most frequent lesson type. Strategies were typically applied during the lesson body and aligned with Standard 3: Plan for and implement effective teaching and learning. Thematic analysis identified eight pedagogical themes, including Learning Through Doing, Constructivist Learning, and Collaborative Learning. Findings demonstrate the utility of TransformUs Higher Ed in promoting PAL adoption within lesson planning, supporting pedagogical competence and alignment with evidence-based teaching standards. Conclusion Embedding PAL-focused interventions within ITE programs can foster pedagogical competence, with lesson planning serving as a crucial step in developing effective, evidence-based teaching practices among future educators.